Interorgan Metabolic Crosstalk in Human Insulin Resistance - Gancheva, Sofiya; Jelenik, Tomas; Álvarez-Hernández, Elisa; Roden, Michael (Physiological reviews, 2018)
Excessive energy intake and reduced energy expenditure drive the development of insulin resistance and metabolic diseases such as obesity and type 2 diabetes mellitus. Metabolic signals derived from dietary intake or secreted from adipose tissue, gut, and liver contribute to energy homeostasis. Recent metabolomic studies identified novel metabolites and enlarged our knowledge on classic metabolites. This review summarizes the evidence of their roles as mediators of interorgan crosstalk and regulators of insulin sensitivity and energy metabolism. Circulating lipids such as free fatty acids, acetate, and palmitoleate from adipose tissue and short-chain fatty acids from the gut effectively act on liver and skeletal muscle. Intracellular lipids such as diacylglycerols and sphingolipids can serve as lipotoxins by directly inhibiting insulin action in muscle and liver. In contrast, fatty acid esters of hydroxy fatty acids have been recently shown to exert a series of beneficial effects. Also, ketoacids are gaining interest as potent modulators of insulin action and mitochondrial function. Finally, branched-chain amino acids not only predict metabolic diseases, but also inhibit insulin signaling. Here, we focus on the metabolic crosstalk in humans, which regulates insulin sensitivity and energy homeostasis in the main insulin-sensitive tissues, skeletal muscle, liver, and adipose tissue.